Workplace wellbeing programmes and their impact on employees and their employing organisations: A scoping review of the evidence base - Fiona Carmichael; S-J. Fenton; M. Pinilla Roncancio; S. Sadhra; M. Sing (University of Birmingham, Birmingham Business School, 2016)
This report constitutes a scoping literature review that identifies and critically examines the evidence base surrounding health and wellbeing programmes conducted in the workplace and their impact on employees and their employing organisations. The review drew on a broad range of sources covering multiple sectors. However, the report additionally highlights evidence that relates specifically to the retail and construction industries. The review offers an analysis of the current evidence base and discusses the implications of implementing different types of workplace health and wellbeing schemes. Some recommendations for supporting and promoting the health and wellbeing of employees in organisations are made on the basis of this review and, where gaps in knowledge are identified, recommendations for further research are made.
Keywords: 330